Vascular risk assessment in female migraineurs - Aysha Zaheer; Shama Iqbal; Sauda Usmani (Journal of University Medical & Dental College, 2026)
BACKGROUND & OBJECTIVES: Migraine is the most common disabling neurological disorder twice as common in females as compared to males. It has been associated to increased vascular risk leading to cardiovascular disease and stroke. The underlying pathophysiology is not yet clear as the results are inconsistent. This study was designed to see if migraine alone, excluding traditional risk factors, is a predictable cause of untoward vascular events. METHODOLOGY: A cross-sectional comparative study was conducted on female migraineurs with a history of varying migraine duration, compared to controls. Participants were divided into three groups of 28 subjects each. Serum homocysteine, highly sensitive C-Reactive Protein and total cholesterol were measured. Data was analyzed with SPSS version 17.0.RESULTS: Median with interquartile range was calculated. Comparison of the groups using the Kruskal-Wallis ANOVA revealed no significant difference among the three groups. The estimated p-value for Hcy, hsCRP and total cholesterol was 0.479, 0.819 and 0.978, respectively.Levels of Hcy, hsCRP, and total cholesterol were also categorised as normal, moderately elevated, and highly elevated. A non-significant difference was observed among the groups.CONCLUSION: The vascular risk profile of migraineurs does not differ from that of healthy females, even if the migraine is present for a longer duration.